ANALISIS KINERJA KEUANGAN DAN PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DALAM BURSA EFEK INDONESIA (TAHUN 2021- 2023) - Anggun Kumala Putri; Fika Amin Nur Aini; Gagah Wardianto; Muis Zainul Abidin; Nabilla Alya Ramanda Putri; Nurlaila Sukma Ayu Sumantri; Ovie Vernanda Ruman Firdaus; Prastica Dewi Larasati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to test and evaluate the effectiveness and expected funding results to increase between 2021 and 2023. The method used is quantitative with data analysis on 10 selected samples using the purposive sampling method. Extreme data is analyzed using a boxplot diagram in SPSS software. Annual financial report data is analyzed through linear regression, and tested using the classical assumption test and hypothesis test. The results of the analysis show that the ROA variable has a t value of -10.259 with a significance of 0.797 (> 0.05), while ROE has a significance of -0.018 and 0.985 (> 0.05). The F value of 0.07 is smaller than F table 3.19, with a significance of 0.929 (> 0.05). This shows that ROA and ROE do not have a significant effect on profit growth. Therefore, further research into other factors that may affect the company's profit growth is needed.